2017
DOI: 10.1002/anie.201705512
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of an Isolated Hydronium Ion in the Interior of Proteins

Abstract: Neutron diffraction analysis studies reported an isolated hydronium ion (H3O+) in the interior of d‐xylose isomerase (XI) and phycocyanobilin‐ferredoxin oxidoreductase (PcyA). H3O+ forms hydrogen bonds (H‐bonds) with two histidine side‐chains and a backbone carbonyl group in PcyA, whereas H3O+ forms H‐bonds with three acidic residues in XI. Using a quantum mechanical/molecular mechanical (QM/MM) approach, we analyzed stabilization of H3O+ by the protein environment. QM/MM calculations indicated that H3O+ was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
(37 reference statements)
2
32
0
Order By: Relevance
“…These results concur with those by Ikeda, et al. that an explicit hydronium ion is unlikely to exist in PcyA, irrespective of the BV protonation state …”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…These results concur with those by Ikeda, et al. that an explicit hydronium ion is unlikely to exist in PcyA, irrespective of the BV protonation state …”
Section: Methodssupporting
confidence: 93%
“…have reported QM/MM studies that explore the possible existence of hydronium ions in PcyA. They used BV with the deprotonated B‐ring and protonated A∼D‐pyrrole rings (referred to as 1B and 1E herein) and noted that a hydronium ion was likely to be unstable …”
Section: Methodsmentioning
confidence: 99%
“…In H-bonds, a proton is more likely to populate the moiety with the higher p K a value between the two moieties 26 . The energy difference between the H-bond donor and acceptor moieties corresponds to the p K a difference and this feature also holds true for H-bonds in protein environments 27 . QM/MM calculations showed that a short H-bond between H 2 O at W1 and D1-Asp61 (O W1 …O D1-Asp61 = 2.45 Å) was formed in the open-cubane S 2 (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…2a ). The potential-energy profile suggested that the O W1 …O D1-Asp61 H-bond is a low-barrier H-bond (LBHB, where the p K a difference for the donor and acceptor moieties is nearly zero 25 , 27 ) (Fig. 2b ), and that the proton is significantly migrated toward D1-Asp61 and delocalized over the two moieties already in S 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5256 Through quantum mechanics/molecular mechanics calculations, Ikeda et al have shown that isolated hydronium ion can stably exist in the interior of proteins when hydrogen bonded with acidic residues, such as aspartic and glutamic acids. 57…”
Section: Resultsmentioning
confidence: 99%